2023
DOI: 10.1371/journal.pone.0288428
|View full text |Cite
|
Sign up to set email alerts
|

Profile of phenolic compounds and antioxidant activity of organically and conventionally grown black-grain barley genotypes treated with biostimulant

Abstract: Beneficial dietary and pro-health values, have resulted in the increasing consumption importance of barley. Therefore, genotypes and cultivation methods are sought that guarantee high functional value of grain. The aim of the study was to assess the content of phenolic acids, flavonoids, chlorophylls, anthocyanidins, phytomelanin and antioxidant activity of grain of three barley genotypes depending on agricultural technology. Two of them are primary genotypes with dark grain pigmentation Hordeum vulgare L. var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the black genotype, elevated levels of total phenolic acids during immature stages led to a consistent AC during this period. Additionally, the synthesis of phytomelanins in black barley, as suggested by Nowak et al [ 11 ], may enhance AC due to their antioxidant properties. Nevertheless, further research is required to elucidate the role of these components in AC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the black genotype, elevated levels of total phenolic acids during immature stages led to a consistent AC during this period. Additionally, the synthesis of phytomelanins in black barley, as suggested by Nowak et al [ 11 ], may enhance AC due to their antioxidant properties. Nevertheless, further research is required to elucidate the role of these components in AC.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in AC observed between the black DHL-191250 and yellow DHL-190849 genotypes could be attributed to phytomelanins, which are responsible for the black color of the grain. Nowak et al [ 11 ] have reported a strong correlation between antioxidant activity and phytomelanins in black barley genotypes, indicating the strong antioxidant properties of these compounds. Among flavonoids, anthocyanins have been associated with high AC [ 51 ], especially when a catechol structure is present in the B ring, as is the case of cyanidin [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that some primary barley genotypes (especially those with dark-colored grains) have particularly high antioxidant potential [13][14][15]. These genotypes are characterized by a higher antioxidant activity and higher concentration of phenolic acids, flavonoids, phytomelanin, lutein, and anthocyanidins than common barley and can be valuable raw materials for the production of functional food [16,17]. The condition for the implementation of these valuable genotypes for cultivation and further consumption use is the recognition of characteristics determining growth, development, and yield in various agroclimatic conditions.…”
Section: Introductionmentioning
confidence: 99%